Challenges and Opportunities Faced by Working Students Amidst Pandemic - JOHN ERWIN PEDROSO; Melchie Liza ALCARDE; Albert Jan Gordon; Clara Belle Ponesto (RADINKA JAYA UTAMA PUBLISHER, 2023)
The COVID-19 pandemic brought drastic changes in various institutions worldwide. It catalysed the implementation of new-normal learning through alternative learning modalities. This descriptive phenomenological study aimed to explore the challenges and opportunities encountered by working students during the pandemic. The researchers have purposively chosen nine (9) working students from a public state university using criteria. A written interview questionnaire was utilized to gather data, which the researchers sent to the informants through the Messenger application. The informants were instructed to answer the question using the Gibbs’ Reflective Model as a guide, where they needed to elaborate the description of their experience, feelings, evaluation, analysis, conclusion, and action plan. The gathered data were analyzed using thematic data analysis. The results included themes such as themes (1) challenges perceived and (2) opportunities gained while working and studying. Further, the researchers generated six (6) categories from the analyzed data. It revealed that working students during the pandemic encounter challenges since they (1) recognize emotional and physical-self limitations and (2) experience lesser in-person connection and mobilization. Regardless, they gained opportunities (3) to develop character and skills, (4) in their finances, (5) to establish a positive outlook, and (6) to develop coping mechanisms. Thus, working students encounter obstacles in this new normal yet obtain benefits integral to their education and personal development.